Search Applications Based Data Analysis Method Boyer Moore - Mulyana A; Purwanto I (International Conference on Engineering and Technology Development (ICETD), 2017)
Can not be denied the technology has evolved very fast today. Almost all modern human use of technology to facilitate the work and life. Each technology has a storage type that is different for each of the data, but the text remains the main form of data storage (Purwoko, 2006). Problems string searching the data store is to find some characters(pattern)in a large amount of text (Hartayo Vembrina, & Meilana, 2011). It can be concluded that the search string or string searching is the search for a pattern of text. Often operating in the text search process involves the emergence of a string, and location of the text in question (Sulistyo, 2006). Because it was the search string is one thing that is needed primarily in search of data. Boyer-Moore algorithm is a string searching algorithm, published by Robert S. Boyer and J. Strother Moore in 1977. Boyer-Moore algorithm is considered to have the best results in practice this algorithm, amatching algorithm moves string on directions right to left